Correction to: Sexual harassment against female nurses: a systematic review - Woldegebriel Gebregziabher Kahsay; Reza Negarandeh; Nahid Dehghan Nayeri; Marzieh Hasanpour (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.